PENGARUH SUGARCANE STREAK MOSAIC VIRUS TERHADAP ANATOMI DAN KADAR KLOROFIL DAUN BEBERAPA AKSESI TEBU (Sacharrum officinarum) - Ruly Hamida; Cece Suhara (BERITA BIOLOGI, 2019)
As one of the most important crops in Indonesia, sugarcane productivity is currently still hampered by Sugarcane Streak Mosaic Virus (SCSMV), with the intensity of leaf damage reach 60% . The symptoms of this disease are the occurrence of irregular pattern between light green to pale in sugarcane leaves.  The information about SCSMV in plant anatomy and physiology was still lacking. Therefore the objective of this studies was to determine the effect of SCSMV infection to morphological, anatomical and physiological characters of sugarcane leaves. The research was performed on 30 sugarcane clones by using a randomized block design with three replications. The results showed that there was change in the morphology of leaves, but leaf color did change. The decrease in the ratio of chlorophyll a / b leaves 65% higher in the resistant clones, i.e. clones PS 06 103 and PS 06 199. The number of stomata also decreased in clones by SCSMV.